Multiferroic properties of Bi0.89Ho0.08Sr0.03Fe0.97−xMn0.03NixO3 thin films modulated by F–N tunneling effects. Issue 11 (1st August 2018) - Guo, Meiyou; Tan, Guoqiang; Yang, Wei; Liu, Yun; Ren, Huijun; Xia, Ao; Lv, Long; Xue, Mintao
Abstract: Bi0.89 Ho0.08 Sr0.03 Fe0.97− x Mn0.03 Ni x O3 (BHSFMNi x O) films were prepared via a chemical solution deposition method. X-ray diffraction (XRD) patterns and Raman spectroscopy revealed that BHSFMNi x O films showed (100) preferential orientation and the structural transition. The structure of BHSFMNi0.02 O was close to the morphotropic phase boundary (MPB) ( R 3 c:H : R 3 m:R = 1:1). The oxygen vacancies were increased with an increase in Ni 2+ doping, and there were many defect dipoles. The BHSFMNi x O thin films exhibited an Ohmic or a space-charge-limited conduction (SCLC) mechanism in a low electric field, and the interface-limited Fowler–Nordheim (F–N) tunneling or the trap-assisted F–N tunneling in a high electric field. The interface-limited F–N tunneling effects of BHSFMNi0.01 O and BHSFMNi0.02 O were due to an interface effect. The large remnant polarizations of BHSFMNi0.01 O and BHSFMNi0.02 O contributed to the intrinsic polarization and the interface-limited F–N tunneling. The fake polarizations of BHSFMNi0.03 O and BHSFMNi0.04 O were dominated by the trap-assisted F–N tunneling in which the interface traps helped the carrier tunnel the potential barrier. These results demonstrate that the polarizations of BHSFMNi x O are related not only to the structural transformation, but also to the defects and conduction mechanisms.